Acetazolamide-Associated Acute Kidney Injury in Critically Ill Pediatric Patients - Moffett, Brady S. (J Pediatr Pharmacol Ther, 2021)
OBJECTIVE: Our objective was to determine the incidence and risk factors for intravenous acetazolamide-associated acute kidney injury (AKI). METHODS: We utilized a retrospective cohort study including patients <19 years of age initiated on intravenous acetazolamide while admitted to an ICU. Data collection included patient demographics, clinical variables, acetazolamide dosing, and serum creatinine (SCr) values. Incidence of AKI was assessed per Kidney Disease Improving Global Outcomes criteria. Descriptive statistical analysis and ordinal logistic regression analysis were performed to determine the incidence of AKI and variables associated with AKI. RESULTS: A total of 868 patients met study criteria (male 55.8%, median age 0.66 years [IQR 0.19, 3.0 years]). Intravenous acetazolamide was administered at 5.1 ± 2.8 mg/kg/dose for a median of 4 doses (IQR 2, 6). Median baseline SCr was 0.28 mg/dL (IQR 0.22, 0.37), corresponding to a creatinine clearance of 115 ± 55 mL/min/1.73 m(2). Acute kidney injury occurred in 26.8% (n = 233) of patients (stage I = 20.1%, stage II = 3.7%, stage III 3.1%), and no patients received renal replacement therapy. An ordinal logistic regression model identified an increased odds of AKI with cyclosporine, ethacrynic acid, and piperacillin-tazobactam administration. CONCLUSIONS: Acute kidney injury occurs frequently in critically ill pediatric patients receiving intravenous acetazolamide.